2021
DOI: 10.3390/ma14020388
|View full text |Cite
|
Sign up to set email alerts
|

Gas Sensor Based on Surface Enhanced Raman Scattering

Abstract: In order to address problems of safety and identification in gas detection, an optical detection method based on surface enhanced Raman scattering (SERS) was studied to detect ethanol vapor. A SERS device of silver nanoparticles modified polyvinylpyrrolidone (PVP) was realized by freeze-drying method. This SERS device was placed in a micro transparent cavity in order to inject ethanol vapor of 4% and obtain Raman signals by confocal Raman spectrometer. We compared different types of SERS devices and found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…SERS is an advanced analytical technique that works on the principle of enhancement of the Raman scattering signals when molecules are located on the roughened metallic surface. [ 11,13,46–48 ] Various analytes such as, soil contaminants, [ 49 ] fluid contaminants, [ 50 ] trace amounts of pesticides on foods, [ 51 ] trace concentrations of air contaminants, [ 52–55 ] explosives, [ 56 ] etc., are dispersed in the diverse environment of liquid, solid, or gaseous phases. It is an important objective to detect such types of targeting analytes with high specificity and sensitivity for healthcare and other purposes.…”
Section: General Features Of Surface‐enhanced Raman Scatteringmentioning
confidence: 99%
“…SERS is an advanced analytical technique that works on the principle of enhancement of the Raman scattering signals when molecules are located on the roughened metallic surface. [ 11,13,46–48 ] Various analytes such as, soil contaminants, [ 49 ] fluid contaminants, [ 50 ] trace amounts of pesticides on foods, [ 51 ] trace concentrations of air contaminants, [ 52–55 ] explosives, [ 56 ] etc., are dispersed in the diverse environment of liquid, solid, or gaseous phases. It is an important objective to detect such types of targeting analytes with high specificity and sensitivity for healthcare and other purposes.…”
Section: General Features Of Surface‐enhanced Raman Scatteringmentioning
confidence: 99%
“…The novelty of leaned pillars with Ag tips was their large aspect ratio, which provided flexibility for leaning towards nearby pillars, creating self-assembled electromagnetic hot spots when illuminated by the laser. A SERS ultrasensitive device to detect ethanol vapor composed of Ag NPs of size 60 nm modified polyvinylpyrrolidone (PVP) was proposed by Wang et al 102 Chen et al 103 demonstrated that Au@ZIF-8 core-shell nanostructures with 55 nm Au NPs and a shell thickness of 3 nm exhibited better SERS response for the detection of various VOC gas molecules, such as toluene, ethylbenzene, and chlorobenzene. Similarly, Xia et al proposed PDMS-coated 1-propanethiol-modification of Au@Ag NPs for enhanced sensitivity of various aromatic vapors in the atmospheric environment.…”
Section: Sers Detection Of Vocs and Other Gasesmentioning
confidence: 99%
“…The novelty of leaned pillars with Ag tips was their large aspect ratio which provided flexibility for leaning towards nearby pillars creating self-assembled electromagnetic hot spots when illuminated by the laser. A SERS ultrasensitive device to detect ethanol vapor composed of Ag NPs of size 60 nm modified polyvinylpyrrolidone (PVP) was proposed by Wang et al[102]. Chen et a [103].…”
mentioning
confidence: 99%
“…The controllable nanostructuring of surfaces by the formation of the nanoparticles of noble metals such as gold, silver and copper, which support the excitation of localized surface plasmon resonance (LSPR), are of increasing interest for a wide range of applications, such as non-linear optics, electronics, catalysis, sensing, enhanced hot-electron and photocurrent generation [ 1 , 2 , 3 , 4 ]. Controlled and reliable field enhancement (FE) effects associated with the excitation of plasmons in resonant metal nanostructures [ 5 , 6 , 7 ] are a potential key to the development of new sensors, and other practical applications of the surface-enhanced Raman spectroscopy (SERS) [ 1 , 8 , 9 , 10 , 11 ]. Silver is one of the metals with excellent plasmonic properties that can be used in the abovementioned fields [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%